Thermal degradation and synthesis of block copolymers of styrene and n-butyl methacrylate by atom transfer radical polymerization - Demirelli, K; Kurt, A; Coskun, M (Taylor & Francis Inc, 2004)
Poly(n-butyl methacrylate) (PnBMA)-b-polystyrene (PS) (diblock), PnBMA-b-PS, and PnBMA-b-PS-b-PnBMA (triblock copolymers) were synthesized by atom transfer radical polymerization (ATRP), using PnBMA and PnBMA-b-PS with C-Br-end-group as macroinitiators. The diblock and triblock copolymers were characterized by H-1-NMR, FT-IR spectroscopy, and differential scanning calorimetry (DSC). The molecular weight and molecular weight distributions were obtained by gel permeation chromatography (GPC). Polymerization was controlled up to a molecular weight of 46,200, and the polydispersity index was 1.33. The experimental results showed that the polymerization was controlled/living. The thermal degradation behavior of the block copolymers was studied using thermogravimetry (TG) and a single line vacuum system consisting of a degradation tube with a condenser for product collection and a liquid nitrogen trap (-196degreesC). The block copolymers were heated from ambient temperature to 500degreesC. The products of degradation were collected at two different fractions, which are cold ring fraction (CRF) and volatile liquid fraction (VLF) trapped at -196degreesC. All the fractions of diblock and triblock copolymers were investigated by means of IR, H-1-NMR, and GC-MS. In this study, n-butyl methacrylate and styrene are given as major products of degradation. On the other hand, the most important minor products are benzene, ethyl benzene, ethyl methacrylate, and toluene.
Keywords: ATRP; styrene; block copolymerization; synthesis; thermal degradation